LIETUVOS FILOSOFIJA – KAIP ISTORIJA, DABARTIS IR ATEITIES VIZIJA - Kardelis, Naglis (Problemos, 2014)
Straipsnis skiriamas šviesiam profesoriaus Romano Plečkaičio atminimui. Straipsnyje analizuojamas Plečkaičio mokslinis palikimas, profesoriaus indėlis į Lietuvos ir visos Vakarų filosofijos istoriją, vertinama teorinis ir asmeninis Plečkaičio vaidmuo Lietuvos filosofijos akademiniame gyvenime ir kultūroje. Straipsnyje teigiama, kad Plečkaitis visų pirma laikytinas filosofijos istorijos kaip solidžios akademinės disciplinos pradininku Lietuvoje, ypač išskirtini jo Viduramžių ir Apšvietos epochos filosfijos istorijos tyrinėjimai. Kita reikšminga Plečkaičio įnašo į lietuviškąjį filosofijos lobyną kryptis – klasikinių tekstų vertimai, ypač pabrėžiant Kanto, Spinozos ir Tomo Akviniečio veikalų pristatymą lietuvių kalba. Atsakomybė, su kuria profesorius vertė Vakarų filosofijos klasikus, formavo akademinio vertimo tradiciją Lietuvoje ir darė įtaką visai Lietuvos kultūrai. Pagrindiniai žodžiai: Romanas Plečkaitis, Vakarų filosofijos istorija, Lietuvos filosofijos istorija. Lithuanian Philosophy – as History, Present and Vision of the Future Naglis Kardelis Abstract The article is devoted to the memory of the late Professor Romanas Plečkaitis. The author presents an evaluation of the extraordinary scholarly achievements of Plečkaitis in the field of the history of philosophy, both Lithuanian and Western in general, discusses the unique force and influence of his professional and personal authority in the context of academic life at the Faculty of Philosophy at Vilnius University, underscores the Professor’s role as one of the most prominent figures in the cultural life of contemporary Lithuania, shares with the reader some private reminiscences from personal communication with the Professor. It is argued that Romanas Plečkaitis was the sole true initiator of the history of philosophy in Lithuania as a solid, scientifically grounded academic discipline. His achievements in various branches of the history of Western philosophy, especially Medieval philosophy and the philosophy of the Enlightenment, are brought to the fore. The superbly conducted translations of the works of various thinkers representing almost all periods of Western philosophy, but especially the translations of the writings of Saint Thomas Aquinas and Immanuel Kant, prominently stand out as an acknowledged classic in the context of Lithuanian philosophical translations. The translations of Plečkaitis with adjacent commentaries as well as precise textual and philosophical analyses are mentioned by the author of this article as being of particular importance to contemporary philosophical discourse in Lithuania and Lithuanian cultural life in general. The achievements of Plečkaitis in the field of the history of Lithuanian philosophy are arguably even more important. In the author’s opinion, the discovery, textual research and philosophical analysis of the extant manuscripts of the philosophy courses taught at various academic institutions of the Grand Duchy of Lithuania at university- and school-level constitute the most valuable part of the Professor’s work in the field of the history of Lithuanian philosophy. The singular role of Romanas Plečkaitis as an informal ambassador of Lithuanian philosophy to other European countries, especially Poland, is also briefly touched upon. Keywords: Romanas Plečkaitis, history of Western philosophy, history of Lithuanian philosophy.